Preunemployment Job Search and Advance Job Loss Notice - Burgess, Paul L.; Low, Stuart A. (Journal of Labor Economics, 1992)
Preunemployment search is the fundamental labor market process generating beneficial effects of advance notice. Yet theory indicates that workers receiving notice may not search, whereas others may search even without advance notice. Our weighted results indicate that over one-third of all nonnotified workers still search and over 40% of workers receiving notice do not respond by searching. Further, preunemployment search determinants differ for notified (nonnotified) workers and men (women). For notified men, search is strongly increased by longer notice and strongly decreased by higher unemployment insurance benefits. But neither factor affects the employed search decisions of notified women.